(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Refractive errors are leading pathology of visual organ among active age population. Myopia is one of the main causes of disability and blindness. Purpose. To assess the clinical outcomes of changes in endothelial cell density, intraocular pressure (IOP), and correlated factors after phakic intraocular lens (IOL) implantation in patients with high myopia during the 6-month postoperative period. Material and Methods. In this observational study, 58 eyes of 30 patients were investigated after spheric implantable collamer lens (ICL) implantation. The main clinical outcomes were uncorrected visual acuity, best-corrected visual acuity, endothelial cell density, intraocular pressure, and correlated factors. In this study, all patients’ postoperative outcomes were evaluated at 1 day, 1 week, 1, 3, and 6 months after surgery. Results. In total, 58 eyes of 30 patients underwent spheric ICL model implantation at the Republican Specialized Scientific and Practical Medical Center of Eye Microsurgery from January 2023 to June 2023. The mean age of patients was 27.52±6.61. The mean preoperative manifest spherical equivalent was -10.59±3.41 D, respectively, which postoperative spherical refractive measures reduced to -0.92±0.37 D. The mean IOP was 15.9±1.92 mm Hg preoperatively. The mean IOP has changed until 15.86±3.3 mm Hg during the 6-month post-operative period. Conclusion. Implantable collamer lens implantation is a safe, effective, and alternative refractive surgery for correction of high myopia in patients with thin corneas and several contraindications for laser correction.